(3TQM ThGgO GHf GdfGXes - (3GdYGedj, eMeO Hf Ydj Hf CHj GdMSfs ((3eMeO MSf Hf eMeO ReGfs)
(3ChdgG (B:s
(3CMSf cdeI jJcde HgG CQHGH GdHjGf(B... (3CeG HYO ajbhd GdabjQ(B... (3ceG Cf GdNdGUI GdCdajI ddagGeI fGOQI(B... (3Cf CLYd dCHjGJg TQMG jPd UYGHgG (B... (3bGd dHjO(B...s
(3BNQgG (B:s
(3GdJCcjO eaSQG HeG dG eRjO Ydjg hGdTGgO aj CHfGA GdgeRI ef Cf jDcO eG ddVQhQI hgPG BNQ eG YgOJg Edi TQMg ef ThGgO TQM CHjGJ GdNdGUI hGdeCehd eef fXQ ajg(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdfMhs